2021
DOI: 10.1177/17085381211035259
|View full text |Cite
|
Sign up to set email alerts
|

Provision of exercise services in patients with peripheral artery disease in the United Kingdom

Abstract: Objectives Supervised exercise programmes (SEPs) are a vital treatment for people with intermittent claudication, leading improvements in walking distance and quality of life and are recommended in multiple national and international guidelines. We aimed to evaluate the use and structure of SEPs in the United Kingdom (UK). Design We conducted an anonymous online survey using the Jisc platform comprising of 40 questions. The survey was designed to address key areas such as access, provision, uptake and delivery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 28 publications
(46 reference statements)
0
14
0
Order By: Relevance
“…Supervised exercise training and secondary cardiovascular prevention are considered a cornerstone for clinical treatment in patients with PAD due to the benefits in different health parameters, such as functional capacity, cardiovascular function, and quality of life [5,7,48,49]. Despite these benefits, in the UK patients has limited access to supervised exercise training in the clinical setting and, patients are not systematically offered evidence-based interventions that support behavioural modification for their risk factors [10]. In addition, a recent study found that financial limitations and travel distances were cited as barriers to participation in supervised exercise training in PAD patients in the UK.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Supervised exercise training and secondary cardiovascular prevention are considered a cornerstone for clinical treatment in patients with PAD due to the benefits in different health parameters, such as functional capacity, cardiovascular function, and quality of life [5,7,48,49]. Despite these benefits, in the UK patients has limited access to supervised exercise training in the clinical setting and, patients are not systematically offered evidence-based interventions that support behavioural modification for their risk factors [10]. In addition, a recent study found that financial limitations and travel distances were cited as barriers to participation in supervised exercise training in PAD patients in the UK.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a recent study found that financial limitations and travel distances were cited as barriers to participation in supervised exercise training in PAD patients in the UK. [10]. To tackle these barriers, we will test the feasibility, acceptability and effectiveness of a home-based exercise and behavioural intervention in patients with PAD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, SEPs have been much less frequently and appropriately endorsed by websites (21/62, 34%). Even though SEPs are endorsed by the NICE and AHA guidelines [ 3 , 16 ], lack of resources and funding often prevent their widespread use in practice [ 31 ]. Therefore, recommendations on websites alone are not enough to improve the management of PAD.…”
Section: Discussionmentioning
confidence: 99%
“… 7 , 8 Structured SET has shown improvements in peak oxygen consumption, pain-free and maximal walking distances, and quality of life. 9 , 10 Despite strong evidence demonstrating the benefits of SET, its availability, adherence, and uptake remain low, 11 13 especially in the US, when compared to antiplatelet therapy, statins, and smoking cessation. 14 Commonly cited barriers include time constraints, travel difficulties, and other personal commitments.…”
Section: Introductionmentioning
confidence: 99%